Role of Heparan Sulfate 2-O-Sulfotransferase in Prostate Cancer Cell Proliferation, Invasion, and Growth Factor Signaling - Brent W. Ferguson; Sumana Datta (Prostate Cancer)
Heparan-sulfate proteoglycans (HSPGs) are required for maximal growth factor signaling in prostate cancer progression. The degree of sulfate modification on the covalently attached heparan sulfate (HS) chains is one of the determining factors of growth factor-HSPG interactions. Sulfate groups are transferred to HS chains via a series of O-sulfotransferases. In the present study, we demonstrate that Heparan sulfate 2-O-sulfotransferase (2OST) is essential for maximal proliferation and invasion of prostate cancer cells in the LNCaP-C4-2B model. We also show that a decrease in invasion due to 2OST siRNA is associated with an increase in actin and E-cadherin accumulation at the cell surface. 2OST expression correlates with increasing metastatic potential in this model. We demonstrate that 2OST expression is upregulated by the stress-inducible transcription factors HIF1α, ATF2, and NFκB. Chromatin immunoprecipitation analysis suggests that HIF1α and ATF2 act directly on the 2OST promoter, while NFκB acts indirectly.